THE IMPLEMENTATION OF RELAXATION AND DISTRACTION TECHNIQUES ON ADOLESCENTS EXPERIENCING ANXIETY IN EARTHQUAKE PRONE AREAS - Yunita Astriani Hardayati; Mustikasari Mustikasari (International Journal of Nursing and Health Services (IJNHS), 2019)
Adolescents are a vulnerable group mental health problem development after frequently being exposed to disaster-related information. Some studies show that adolescent living in earthquake-prone areas experience anxiety. Adolescents’ untreated anxiety possibly causes mood disorders, eating disorders, and even anxiety disorder. Nursing intervention conducted to reduce anxiety consists of relaxation and distraction techniques. Relaxation techniques consist of deep breathing exercises and five-finger relaxation techniques. This case study aims to describe the change signs and symptoms of anxiety on adolescent in earthquake prone area that giving relaxation and distraction techniques. The subjects of this study were four high-school-adolescent-students suffering from moderate anxiety about earthquake and were measured by Hamilton Anxiety Rating Scale (HARS). The results reveal that anxiety levels of all subjects decreases with average HARS score is 11,5. It is concluded that relaxation and distraction techniques can use as one of theraphy to reduce anxiety on middle adolescent in earthquake- prone area. This case study is considered as an important reference material for practitioners who find a similar case in the pratice setting.